Antibiotic Resistance and Virulence Profiles of Klebsiella pneumoniae Strains Isolated From Different Clinical Sources - Ballén, Victoria; Gabasa, Yaiza; Ratia, Carlos; Ortega, Raquel; Tejero, Marc; Soto, Sara (Frontiers in Cellular and Infection Microbiology, 2021)
Klebsiella pneumoniae is a Gram-negative bacterium capable of colonizing, invading, and causing infections in different anatomical sites of the human body. Its ability to evade the immune system, its increasing antimicrobial resistance and the emergence of hypervirulent pathotypes have become a major challenge in the medical field. In this study, 127 strains from different clinical sources (urine, respiratory tract or blood) were characterized for antimicrobial resistance, the presence of virulence factor genes, serum resistance, hypermucoviscosity and the ability to form biofilms. Specific characteristics of the uropathogenic strains were examined and compared with the other clinical groups. Differences were found between urine and the other groups of strains. Urine strains showed the highest antibiotic resistance (64.91%) compared to blood (63.64%) or respiratory strains (51.35%) as well as the highest extended-spectrum beta-lactamases (ESBL) production. These strains also showed statistically significant high resistance to fosfomycin (24.56%) compared to the other groups (p = 0.008). Regarding virulence, 84.21% of the urine strains presented the uge gene, showing a statistically significant difference (p = 0.03) compared to the other clinical sources, indicating a possible role of this gene in the development of urinary tract infection. In addition, 46% of biofilm-forming strains belonged to the urine sample group (p = 0.043). In conclusion, K. pneumoniae strains isolated from urine samples showed higher antimicrobial resistance, ESBL production, and biofilm-forming ability compared to those isolated from respiratory or blood samples. The rapid spread of clinical strains with these characteristics is of concern, and new therapeutic alternatives are essential to mitigate their harmful effects.